'I've got my Sat Nav, it's alright': Users' Attitudes towards, and Engagements with, Technologies of Navigation. (November 2015) - Speake, Janet
Abstract : The use of qualitative research techniques in a largely quantitative cartographic domain is opening up myriad ways to explore users' engagements technologies of navigation. This study draws on young UK-based students' real words and life experiences as they engage with Satellite Navigation and other wayfinding technologies during first-time visits to new places to reflect on the nature of the changing relationships between self, navigational object, space and place.